Synthesis And Characterisation Of Pegylated Gold Nanoparticles For Enhancement Of Agglutination Reaction In Antibody Screening Test - Ishak, Nordiyana (2024)
Red blood cell (RBC) antigen-antibody agglutination is a crucial reaction in antibody screening tests (AST) to identify the presence of unexpected clinically significant antibodies in the plasma recipient. However, with the current method using low-ionic strength solution (LISS) as an enhancement medium for detecting antibody in AST, several drawbacks such as the missing detection of some clinically significant antibodies, and thus, can cause an adverse transfusion reaction. Hence, a new solution using polyethylene glycol with molecular weight of 4000 (PEG4000) conjugated with gold nanoparticles (AuNPs) was synthesised to produce a better RBC antigen-antibody agglutination enhancement capacity in AST. The synthesised PEG-AuNPs solution was characterised for optical properties by Ultraviolet-Visible Spectroscopy (UV-Vis), morphological characterisation by Energy-Filtered Transmission Electron Microscopy (EFTEM) and Field Emission Scanning Electron Microscope (FESEM), particle size and zeta potential analysis by Dynamic Light Scattered (DLS), and structural and composition of bonding material by Fourier-transform infrared (FT-IR) spectroscopy. Then, the RBC agglutination scoring using tube method was compared between the synthesised solution with standard LISS in AST using 120 samples consisted of 60 negative and 60 positive samples of antibody. The final colour of the solution changed to ruby red indicating the successful formation of PEG-coated with AuNPs.